2016
DOI: 10.1186/s12905-016-0328-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender at the intersection with race and class in the schooling and wellbeing of immigrant-origin students

Abstract: BackgroundIn French-language secondary schools in Quebec, among all immigrant-origin students, those originating from South Asia have the highest dropout rate. However, girls belonging to this group consistently outperform their male peers of similar ethnic background. This stirs questions about the reasons for this relative outperformance and its linkage with overall wellbeing among these girls.MethodsA mixed methods approach guided data collection. It involved in-depth interviews with female and male student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Patel and Gaw (1996) also found that younger Indianorigin women in the United States were at higher risk for suicide than their male and older female counterparts. Interestingly, Bakhshaei and Henderson (2016) found that SA female adolescents in Quebec outperform their male counterparts in schooling attainment due to parental expectations, socialization at home and relationships at school.…”
Section: Acculturation Issuesmentioning
confidence: 99%
“…Patel and Gaw (1996) also found that younger Indianorigin women in the United States were at higher risk for suicide than their male and older female counterparts. Interestingly, Bakhshaei and Henderson (2016) found that SA female adolescents in Quebec outperform their male counterparts in schooling attainment due to parental expectations, socialization at home and relationships at school.…”
Section: Acculturation Issuesmentioning
confidence: 99%
“…17 Many of the studies based in the global south examine migration -from violence among internally displaced youth in Haiti 18 to the plight of Syrian refugees in Lebanon 19 and HIV risks for Pakistani labor migrants in the Persian Gulf. 20 Much of the published work on structural violence in the global north has focused on immigrant groups, [21][22][23] indigenous peoples, 24 and marginalized populations such as the homeless. 25,26 Some of the papers in this group invoked structural violence as a lens to analyze domestic violence.…”
Section: Use Of "Structural Violence" In Health Studiesmentioning
confidence: 99%
“…Much of the published work on structural violence in the global north has focused on immigrant groups, 2123 indigenous peoples, 24 and marginalized populations such as the homeless. 25,26 Some of the papers in this group invoked structural violence as a lens to analyze domestic violence.…”
Section: Use Of “Structural Violence” In Health Studiesmentioning
confidence: 99%
“…Moreover, only a small proportion of them has French as mother tongue or as language used at home (4.0%). Within this target group, there is also an important overrepresentation of boys and concomitant underrepresentation of girls (55.0% vs. 45.0%), which, consistent with national and international research (Canadian Education Statistics Council, 2014;Jacob, 2002;Machin & McNally, 2005), could pose a disadvantage to this group's academic success (Bakhshaei & Henderson, 2016). Furthermore, the families of this group have a strongly disadvantaged socioeconomic profile with a marked overrepresentation in the weakest socioeconomic status category (67.0%), a trend that has been found in other studies to pose a potential disadvantage to school success (Sirin, 2005;White, 1982).…”
Section: Discussionmentioning
confidence: 96%